Update on Cancer Screening Recommendations for Individuals with Li-Fraumeni Syndrome - Achatz, Maria Isabel; Villani, Anita; Bertuch, Alison A.; Bougeard, Gaëlle; Chang, Vivian Y.; Doria, Andrea S.; Gallinger, Bailey; Godley, Lucy A.; Greer, Mary-Louise C.; Kamihara, Junne; Khincha, Payal P.; Kohlmann, Wendy K.; et al. (Clinical cancer research, 2025)
Abstract - Li-Fraumeni syndrome (LFS) is an autosomal dominant cancer predisposition condition characterized by a high lifetime risk for a wide spectrum of malignancies associated with germline pathogenic/likely pathogenic variants in the TP53 tumor suppressor gene. Secondary malignant neoplasms are particularly common. Early cancer detection through surveillance enables early intervention and leads to improved clinical outcomes with reduced tumor-related mortality and treatment-related morbidity. Since the 2017 publication of LFS tumor surveillance guidelines from the inaugural American Association for Cancer Research Childhood Cancer Predisposition Workshop, understanding the genotype-phenotype relationships in LFS has evolved, and adaptations of the guidelines have been implemented in institutions worldwide. The “Toronto Protocol” remains the current standard for lifelong surveillance; however, as outlined in this perspective, modifications should be considered about the use of certain modalities to target organs in an age-dependent manner. The Working Group’s recommendations have also been extended to include a more detailed outline for surveillance in the adult TP53 pathogenic/likely pathogenic variant carrier population, based on the recognition that early education of both practitioners and patients on what to expect after the transition from childhood/adolescence to young adulthood is important in preparing them for changes in surveillance strategies. In this perspective, we provide an up-to-date clinical overview of LFS and present our updated consensus tumor surveillance recommendations from the 2023 American Association for Cancer Research Childhood Cancer Predisposition Workshop.
Gesehen am 27.10.2025